SOLUTION OF THE PROBLEM OF OIL-POOL IN-SITU COMBUSTION FRONT PROPAGATION ON THE BASIS OF HEURISTIC HYPOTHESIS REGARDING TEMPERATURE AND CONCENTRATION PROFILES - K. V. Dobrego (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
At present the number of oil deposits with viscous and stranded oil is steadily growing. Due to the mentioned circumstance there is growing interest in methods of thermochemical treatment of an oil and coal-beds. This interest is reflected, e.g., in the “Visha-Thermogaz” BelarusianRussian joint project. In order to provide control over the in-situ thermochemical processes it is necessary to use models of different levels, i.e. qualitative analysis, simplified numerical simulation with “averaged” parameters, as well as detailed 2D and 3D modeling. Due to variety of specific parameters and conditions of in-situ processes, design of new simplified methods of analysis is a topical objective both for research and practical activity. Therefore, a new method of solution of the problem of in-situ combustion front propagation based on heuristic hypothesis is discussed in the present article. The designed method is based on heuristic assumption of functional relationship between the profiles of temperature T and deficit component concentration y: exp(-E / T ) = exp(-E / Tmax )(1- y). Another hypothesis is the assumption that the maximum gradient of the concentration profile of the missing component is implemented with a fixed value of concentration that is expressed as y’’ ( y = y*) = 0. Simple algebraic and differential equations fordetermination of the temperature and concentration profiles as well as for the front propagation velocity are derived for two cases i.e. the lack of oxidizer and the fuel component fault. Principal functional dependencies of the front velocity are revealed. Comparison of the profiles obtained with the use of the described method with the one obtained numerically proves the adequacy of the method itself and the hypotheses adopted. The method can be used for rapid assessment and parametric studies of the profiles and the speed of the front. It can also be used for analysis of similar problems of chemical and heat engineering.